دور الإستقامة التنظيمية كمتغير وسيط في العلاقة بين القيادة الأبوية والمخرجات الوظيفية بالجامعات المصرية: دراسة تطبيقية - طه، منى حسنین السید (جامعة المنوفية - كلية التجارة, 2021)
استهدف هذا البحث، تحديد مستوى تطبيق القيادة الأبوية من وجهة نظر أعضاء هيئة التدريس بالجامعات المصرية الحكومية والخاصة محل الدراسة، وتحديد مستوى الاستقامة التنظيمية من وجهة نظرهم، وتحديد مستوى المخرجات الوظيفية بالجامعات المصرية محل الدراسة، وتحديد نوع وقوة العلاقة بين القيادة الأبوية والمخرجات الوظيفية، ونوع وقوة العلاقة بـين القيادة الأبويـة والاستقامة التنظيمية، ونوع وقوة العلاقة بين الاستقامة التنظيمية والمخرجات الوظيفية، ونوع وطبيعة العلاقة بين القيادة الأبوية والمخرجات الوظيفية في وجود الاستقامة التنظيمية كمتغير وسيط، ولتحقيق ذلك تم الاعتماد على قائمة الاستقصاء لجمع البيانات الأولية باستخدام عينة قوامها ٣٣٩ عضو هيئة تدريس بالجامعات المصرية الحكومية، و٢٦٨ عضو هيئة تدريس بالجامعات المصرية الخاصة، وقد أظهرت نتائج الدراسة الميدانية ارتفاع مستوى ممارسة قيادات الجامعات المصرية محل الدراسة لنمط القيادة الأبوية من وجهة نظر أعضاء هيئة التدريس بالجامعات محل الدراسة، وارتفاع مستوى الاستقامة التنظيمية، وأن مستوى المخرجات الوظيفية متوسط، ووجود علاقة طردية ذات دلالة إحصائية بين أبعاد القيادة الأبوية والاستقامة التنظيمية، ووجود علاقة طردية ذات دلالة إحصائية بين أبعاد القيادة الأبوية والمخرجات الوظيفية، ووجود علاقة طردية ذات دلالة إحصائية بين الاستقامة التنظيمية والمخرجات الوظيفية، ووجود علاقة غير مباشرة وذات دلالة إحصائية بين القيادة الأبوية والمخرجات الوظيفية من خلال الاستقامة التنظيمية كمتغير وسيط، كما دعم وجود الاستقامة التنظيمية كمتغير وسيط في العلاقة بين القيادة الأبوية والمخرجات الوظيفية بالجامعات المصرية الحكومية والخاصة محل الدراسة من تأثير أبعاد القيادة الأبوية على مستوى المخرجات الوظيفية. وفي نهاية البحث، تم التوصل إلى عدد من التوصيات التي تساعد في تحسين المخرجات الوظيفية للجامعات المصرية من خلال تطبيق واستخدام مبادئ وأبعاد القيادة الأبويـة والاستقامة التنظيمية.
This research aimed to determine the application level of paternalistic leadership from faculty members in the Egyptian public and private universities point of view. Also, determine the level of organizational virtuousness from their point of view, as well as determine the level of job outputs in the Egyptian universities under study, and determine the type and strength of the relationship between paternalistic leadership and job outcomes, and the type of The strength of the relationship between paternalistic leadership and organizational virtuousness, the type and strength of the relationship between organizational virtuousness and job outcomes, and the type and nature of the relationship between paternalistic leadership and job outcomes in the presence of organizational virtuousness as a mediating variable. The results of the field study showed a high level of practice by the leaders of the Egyptian universities under study of paternalistic leadership style from the faculty members in the universities under study point of view. Moreover, high level of organizational virtuousness, and that the level of job outputs is average, and the presence of a direct statistically significant relationship between the dimensions of the Paternalistic leadership and organizational virtuousness, the presence of a direct statistically significant relationship between the dimensions of paternalistic leadership and job outcomes, and the existence of a direct statistically significant relationship between organizational virtuousness and job outcomes, and the presence of an indirect and statistically significant relationship between paternalistic leadership and job outcomes through organizational virtuousness as a mediating variable. Supporting the existence of organizational virtuousness as a mediating variable in the relationship between paternalistic leadership and job outcomes in the Egyptian public and private universities under study from the impact of paternalistic leadership dimensions on the level of job outcomes. At the end of the research, a number of recommendations were reached that help improve the job outcomes of Egyptian universities through the application and use of the principles and dimensions of paternalistic leadership and organizational virtuousness.
Keywords: الجامعات -- القيادة الجامعية -- القيادات الجامعية -- القيادة الأبوية -- الإستقامة التنظيمية -- المخرجات الوظيفية -- أعضاء هيئة التدريس -- الجامعات المصرية